Is "Big Gear" effective for road cyclists? A coach`s standpoint to guide decision-making - Dantas, J. L. (Journal of Science and Cycling, 2025)
"Big Gear" training, a common low-cadence strategy among road cyclists, involves pedalling at 40-60 rpm under high torque, typically at or just below Functional Threshold Power. Despite its widespread use and perceived similarity to resistance training, Big Gear training effectiveness remains debated. This viewpoint critically examines the evidence surrounding Big Gear training role in enhancing muscular strength, endurance, and overall performance in road cyclists. Contrary to popular belief, Big Gear training does not meet the intensity threshold required to induce strength adaptations comparable to traditional resistance training. Evidence shows that Big Gear training produces lower neuromuscular strain and operates at <50% of Maximal Dynamic Force—well below the >60% threshold needed for strength gains. Furthermore, studies indicate that resistance training leads to greater improvements in maximal force production than Big Gear training. Similarly, Big Gear training shows no consistent advantage in promoting endurance adaptations or performance outcomes. Notably, studies that suggest benefits of low-cadence training often employ cadences and intensities higher than those typical of Big Gear training protocols. Some evidence even raises concerns about potential negative effects of Big Gear training on key performance determinants. In conclusion, the available evidence suggests that Big Gear training is either ineffective or, at best, questionable, being insufficient to trigger the positive adaptations associated with low-cadence training. It is recommended that coaches consider the efficacy of traditional Big Gear training in comparison to protocols that have been demonstrated to have more robust evidence-based outcomes.